Whitewashed adobe : the rise of Los Angeles and the remaking of its Mexican past - Deverell, William, 1962- (University of California Press, 2004)
Chronicling the rise of Los Angeles through shifting ideas of race and ethnicity, William Deverell offers a unique perspective on how the city grew and changed. Whitewashed Adobe considers six different developments in the history of the city--including the cementing of the Los Angeles River, the outbreak of bubonic plague in 1924, and the evolution of America's largest brickyard in the 1920s.